The next level of 3D tumour models: immunocompetence. Issue 9 (September 2016) - Nyga, Agata; Neves, Joana; Stamati, Katerina; Loizidou, Marilena; Emberton, Mark; Cheema, Umber
Highlights: There is increasing interest in the role of immune cells in cancer progression. Move from 2D in vitro research to 3D complex disease models. 3D models are used to study interactions between cancer cells, stroma and immune cells. Abstract : The complexity of the tumour microenvironment encompasses interactions between cancer and stromal cells. Moving from 2D cell culture methods into 3D models enables more-accurate investigation of those interactions. Current 3D cancer models focus on cancer spheroid interaction with stromal cells, such as fibroblasts. However, over recent years, the cancer immune environment has been shown to have a major role in tumour progression. This review summarises the state-of-art on immunocompetent 3D cancer models that, in addition to cancer cells, also incorporate immune cells, including monocytes, cancer-associated macrophages, dendritic cells, neutrophils and lymphocytes.